The use of policresulen concentrate in the management of hypergranulation in diabetic foot ulcers: A case report - Ritonga, Sukhri Herianto; Rangkuti, Juni Andriani; Lubis, Arisa Harfa Said; Nasution, Nur Arfah (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Diabetic foot ulcers are a severe complication of diabetes, causing pain, infection risk, and reduced quality of life. Timely and effective wound management is crucial to prevent delayed healing, which may ultimately result in amputation. One of the complications often encountered in diabetic foot ulcers is hypergranulation tissue. Policresulen, known for its hemostatic and antimicrobial properties, presents a potential option for managing hypergranulation. This case report explores the effects of applying policresulen concentrate to a diabetic foot ulcer complicated by hypergranulation tissue. The case involved a 61-year-old male patient with a 15-year history of diabetes mellitus which developed a diabetic foot ulcer two years prior. Despite 10 months of various treatments, wound healing remained suboptimal due to persistence hypergranulation tissue. Policresulen concentrate was applied every three days for a total of 16 wound care sessions, and healing progress was evaluated using the Bates-Jensen Wound Assessment Tool. Over the course of treatment, the hypergranulation tissue gradually diminished, and the wound progressively closed until complete epithelialization was achieved. This case demonstrates that policresulen concentrate may be effective in managing hypergranulation and facilitating wound closure in diabetic foot ulcers. No adverse effects were observed during the treatment period.